Development of Insulation for High Flux Density Receivers. (May 2015) - Ebert, M.; Arnold, W.; Avila-Marin, A.; Denk, T.; Hertel, J.; Jensch, A.; Reinalter, W.; Schlierbach, A.; Uhlig, R.
Abstract: In the last years more experience has been achieved with long time operation of solar tower receivers increased in size. The insulation of these receivers shows higher complexity and importance compared to small prototypes [1, 2]. Both insulation of tubular cavity receiver and inner insulation of piping are safety-relevant components as they protect e.g. support structures and pressurized tubes and connections against overheating. Besides safety, operating reliability is one of the most important requirements to meet as down times, maintenance and repairs cause high costs. This paper describes the new development of the insulation for a tubular cavity receiver with air as heat transfer medium, where costs and thermal heat loss should be reduced. The prototype has been designed, built and tested for 100 operating hours at receiver outlet temperatures of up to 800 °C at the test facility Plataforma Solar de Almería (PSA), Spain. The results of a thermal model, of material tests and the evaluation of the thermal heat loss are presented.